Pengembangan Aplikasi Layanan Kesehatan berbasis Web untuk Skrining Pendengaran menggunakan Arsitektur Clean (Studi Kasus: Fakultas Kedokteran Universitas Brawijaya) - Harun Ulum Fajar; Agi Putra Kharisma; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The COVID-19 pandemic has had an impact on society. Interaction restrictions lead to the accessibility of public services, including public health services. Currently, the Faculty of Medicine, Universitas Brawijaya has conducted an online hearing screening process. However, it still does not meet the needs of doctors. The author initiated a research entitled "Development of Web-Based Health Service Applications for Hearing Screening (Case Study: Faculty of Medicine, Universitas Brawijaya)". The author chooses to use Clean Architecture by considering the ease of developing applications without the need to focus on a particular framework. The application is developed on the web so that it can be accessed through a browser. There are 3 tests, namely: functional testing, compatibility testing, and usability testing. In functional testing has been achieved 100% valid. The patient actor usability test got an A+ grade, the doctor actor got a C grade, and the Admin actor got an A grade. Compatibility testing has been running well on Chrome, Safari, Edge and Firefox browsers.